Use of Diagnostic Algorithms for NTRK Fusion-Positive Tumors in Pathology Institutes in Switzerland - Holger Moch; Gieri Cathomas; Milo Frattini; Wolfram Jochum; Erik Vassella; Laurence de Leval; Joachim Diebold; Christian Britschgi; Thomas McKee; Lukas Bubendorf (healthbook TIMES. Oncology Hematology, 2021)
In May 2020, larotrectinib (Vitrakvi®) was approved as the first tumor-agnostic agent in Switzerland for the treatment of adult and pediatric patients with solid tumors that have a neurotrophic tyrosine receptor kinase (NTRK) gene fusion. While in certain types of tumors an NTRK gene fusion is often detectable, it is rare in some other types. As the detection of NTRK gene fusion opens up new treatment options for patients, it is vital to ensure that the detection methods and diagnostic algorithms in pathology institutes are optimized and of high quality. Detection can be performed by immunohistochemistry, next-generation sequencing or by fluorescence in situ hybridization. This review will discuss diagnostic algorithms based on underlying pathology that can be recommended for the detection of NTRK gene fusions in Switzerland.